Following the sun The pioneering years of solar energy research at The Australian National University 1970-2005 - Tennant-Wood, Robin (ANU Press, 2012)
In 1970 a small group of physicists at The Australian National University decided to veer away from the accepted and expected directions in energy research and pursued the emerging discipline of solar energy. Over the next decade ANU joined a small cluster of research institutions, including the CSIRO, UNSW and the University of Sydney, to emerge as a world leader in solar energy technology. This book traces the history of solar energy research at ANU over 35 years from its origin, its sometimes controversial early stages, through its flagship projects to its current status as one of the world's best known solar energy research establishments. It is as much a story of the future as it is a history: Following the sun is the story of how an idea to pursue what was in 1970 a new and unpopular research path has come to underpin sustainable development in the 21st Century.